The Lysenko Controversy as a Global Phenomenon, Volume 2
XI, 243 p. 1 illus. in color.
Keywords: This volume examines the international impact of Lysenkoism in its namesake’s heyday and the reasons behind Lysenko’s rehabilitation in Russia today. By presenting the rise and fall of T.D. Lysenko in its various aspects, the authors provide a fresh perspective on one of the most notorious episodes in the history of science.